Effects of Exercise and Calorie Restriction on Brain_x000D_ and Testis in Natural Aging Model - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK; ŞENER, GÖKSEL; AKBAY, TUĞBA (My University, 2021)
The aim of our study was to examine the effects of exercise and calorie_x000D_ restriction on various tissue damage and antioxidant parameters_x000D_ in the brain and testis of rats in a natural aging model. For this_x000D_ purpose, male Sprague-Dawley rats were the control group (C),_x000D_ the elderly (A), the elderly with calorie restriction (ACR), the elderly_x000D_ who were exercised (AE) and the elderly who were exercised with_x000D_ calorie restriction (ACRE), they were divided into 5 groups. The control_x000D_ group was composed of three-month-old animals. The other_x000D_ group consisted of 15-month-old rats. Exercise and calorie restriction_x000D_ were applied for 6 weeks. At the end of the experiment, lipid_x000D_ peroxidation (LPO), nitric oxide (NO), glutathione (GSH) levels and_x000D_ superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase_x000D_ (GST) and tissue factor (TF) were determined in brain and_x000D_ testicular tissues homogenates. As a result of the study, the A_x000D_ group’s brain and testis LPO, NO levels and TF activity increased,_x000D_ GSH levels and SOD, CAT and GST activities decreased, when compared_x000D_ to the C group. As a result of our study, an increase in oxidant_x000D_ damage was observed with TF activity in the brain and testis in the_x000D_ natural aging model, and positive effects of exercise and calorie_x000D_ restriction on the antioxidant levels in the brain were determined,_x000D_ especially in aging.

Amacımız doğal yaşlanma modelinde egzersiz ve kalori kısıtlamasının_x000D_ sıçanlarda beyin ve testiste çeşitli doku hasarı ve antioksidan_x000D_ parametreler üzerine etkilerinin incelenmesidir. Bu amaçla Sprague-_x000D_ Dawley sıçanlar kontrol (K), yaşlı (Y), kalori kısıtlaması uygulanan_x000D_ yaşlı (YKK), egzersiz uygulanan yaşlı (YE) ve kalori kısıtlaması ile_x000D_ egzersiz uygulanan yaşlı (YKKE) olmak üzere 5 gruba ayrıldı. Kontrol_x000D_ grubu üç aylık genç hayvanlardan oluşturuldu. Diğer gruplar_x000D_ 15 aylık sıçanlardan oluşturuldu. Egzersiz ve kalori kısıtlaması 6_x000D_ hafta boyunca uygulandı. Deney sonunda beyin ve testis dokuları_x000D_ homojenatlarında lipit peroksidasyon (LPO), nitrik oksit (NO), glutatyon_x000D_ (GSH) düzeyleri ile süperoksit dismutaz (SOD), katalaz (CAT),_x000D_ glutatyon-S-transferaz (GST) ve doku faktörü (DF) aktiviteleri tayin_x000D_ edildi. Çalışma sonucunda K grubu ile kıyaslandığında Y grubunda,_x000D_ beyin ve testis LPO, NO düzeyleri ve DF aktivitelerinin arttığı, GSH_x000D_ düzeyleri ile SOD, CAT ve GST aktivitelerinin ise azaldığı gözlendi._x000D_ Doğal yaşlanma modelinde beyin ve testiste DF aktivitesi ile beraber_x000D_ oksidan hasarda artış gözlenmiş olup, özellikle yaşlanmada_x000D_ egzersiz ve kalori kısıtlamasının beyinde antioksidan düzeyleri üzerinde_x000D_ olumlu etkileri belirlenmiştir.
Doğal Yaşlanma Modelinde Egzersiz ve Kalori Kısıtlamasının Beyin ve Testiste Etkileri